Myoepithelial Carcinoma Spindle cell type, Clear cell type, and Plasmacytoid type: Serial Kasus A Case Series of Myoepithelial Carcinoma Spindle cell type, Clear cell type, and Plasmacytoid type - Lestari, Dian Yuliartha; Fauziah, Dyah (Universitas Muhammadiyah Semarang, 2018)
Myoepithelial Carcinoma adalah salah satu keganasan kelenjar liur yang sangat jarang terjadi, dimana terdiri dari komponen sel-sel myoepithelial yang berdifferensiasi sebagai sel spindle, sel jernih (clear), sel epitheloid, sel stelate, maupun sel plasmacytoid.Kami melaporkan 3 kasus myoepithelial carcinoma yang didiagnosis di Rumah Sakit Dr. Soetomo Surabaya dalam kurun waktu 4 tahun terakhir dengan tiga tipe yang berbeda, yaitu; spindle cell type, clear cell type, dan plasmacytoid type. Dua kasus terjadi pada kelenjar parotis, lainnya pada kelenjar submandibula, dimana ketiganya terjadi pada wanita dengan rentang usia 45-76 tahun. Keluhan saat datang berobat adalah timbul benjolan semakin membesar secara perlahan dan tidak menimbulkan nyeri. Hasil pemeriksaan histopatologis menyatakan suatu carcinoma mengesankan myoepithelial carcinoma. Hasil pemeriksaan immunohistokimia smooth muscle actin (SMA)dan S100 mayoritas menunjukkan hasil yang positif, dimana menyokong diagnosis suatu myoepithelial carcinoma Myoepithelial Carcinoma is one of the most rare salivary gland malignancies, which consists of components of myoepithelial cells that differentiate as spindle cells, clear cells, epitheloid cells, stellate cells, and plasmacytoid cells.We report 3 cases of myoepithelial carcinoma diagnosed at Dr. Hospital. Soetomo Surabaya in the last 4 years with three different types, namely; spindle cell type, clear cell type, and plasmacytoid type. Two cases occurred in the parotid gland, the other in the submandibular gland, of which all three occurred in women with a range of45-76 years old. Complaints when coming for treatment is a lump that grows slowly and does not cause pain. The results of histopathological examination revealed a carcinoma suggesting myoepithelial carcinoma. The results of the immunohistochemical examination of smooth muscle actin (SMA) and S100 the majority showed positive results, which supported the diagnosis of myoepithelial carcinoma.